An Examination of the Media Portrayal of Femicide–Suicides: An Exploratory Frame Analysis. (January 2014) - Richards, Tara N.; Gillespie, Lane Kirkland; Smith, M. Dwayne
Recent research has been focused on the portrayal of intimate partner homicides in the news media with specific emphasis on the most commonly occurring type, femicides (the murder of a female intimate partner by a male intimate partner). One important finding in the analysis of intimate partner homicide is the striking number of femicides that are followed by perpetrator suicide. Whereas homicide followed by suicide is a rare occurrence in the context of crime generally, within the context of intimate partner homicide, femicide–suicide is common. The present research utilized content analysis to explore the media coverage of a near population of femicide–suicide cases in the North Carolina from 2002 to 2009 ( n = 86). An examination of the article titles showed that the majority of titles (54%) assigned to the articles describe the crime as an ambiguous homicide or homicide–suicide and do not indicate the relationship between the perpetrator and victim. In comparison, results show that 78% of the articles' text defined the homicide–suicide as domestic violence. Specifically, in cases where the news coverage defined the femicide–suicide as domestic violence, the authors identified 4 media frames used (1) femicide–suicide by a male perpetrator, (2) femicide–suicide due to loss of perpetrator control, (3) femicide–suicide as a mercy killing, and (4) femicide–suicide due to jealousy. Implications for societal perceptions of violence against women as well as corresponding victims' policies/services are presented and discussed.